Arm coordination adaptations assessment in swimming - Schnitzler, C.; Seifert, L.; Ernwein, V.; Chollet, D. (International Journal of Sports Medicine, 2008)
The link between modifications in arm coordination (IdC) and intracyclic velocity variation (IVV) as a function of swim pace and gender is investigated. Twelve elite swimmers performed 5 different swim paces. Video analysis allowed IdC determination. The IVV was determined with a velocity-metre system. Results showed (i) a significant increase in IdC with swim pace (p < 0.05) but no significant change in IVV, and (ii) a gender effect for the mean values of both IdC and IVV (p < 0.05). This suggests that (i) the increase in IdC with swimming velocity helps to maintain IVV stability, and (ii) the mean IdC and the IVV level are determined by the relationship between anthropometric parameters and mechanical power output. Indeed, compared to males, the females generally had a lower mechanical power output, and lower drag to overcome, which explains the lower IVV found. It was concluded that increasing IdC could be a strategy adopted by elite swimmers to maintain IVV at a constant level, despite increases in both propulsive and drag forces and in relation to individual characteristics. Thus, the IVV-IdC relationship may be an interesting tool to determine a swimmer's misadaptation to the swim pace and to orient individual coaching in coordination analysis.